Efficacy and safety of cyclin dependent kinases 4/6 inhibitors in the treatment of metastatic breast cancer: a real-world experience. (1st November 2020) - Edman Kessler, Luisa; Wiklander, Oscar; Hamberg, Eva; Bergh, Jonas; Foukakis, Theodoros; Matikas, Alexios
Abstract: Background: Randomized trials have shown survival gains for patients with metastatic breast cancer (BC) treated with CDK4/6 inhibitors (CDK4/6i) in combination with endocrine agents. It is not unlikely that there may be discrepancies between the generally fit clinical study population and the real-world setting that could affect adherence to treatment guidelines, tolerance to treatment and outcome. Material and methods: Consecutive patients with metastatic or locally advanced and unresectable BC that were treated between July 2017 and January 2020 at Karolinska University Hospital, Stockholm, Sweden and that had received at least one dose of CDK4/6i were included in this retrospective study. The primary endpoint was safety, including toxicity according to CTCAE 5 and rates of treatment interruptions, dose reductions and discontinuations. The secondary endpoint was efficacy based on the treating physicians' assessments in terms of progression free (PFS) and overall survival (OS), as well as the factors associated with patient outcome. Results: Eighty-eight patients were included in the analysis, with a median age of 67.2 years. Grade 4 neutropenia occurred in 9.1% of patients and one episode of neutropenic infection was observed. Dose reductions were made in 38.6% of patients, while 11.4% discontinued treatment due to toxicity, most commonly non-hematologic. After a median follow-up of 18.33 months, median PFS was 13.30 months (95% CI, 11.39–15.21) and median OS could yet not be estimated. In multivariable analysis, number of prior chemotherapy lines was an independent predictor for shorter PFS (HR = 3.28, 95% CI 1.50–7.16, p = .003). Conclusions: CDK4/6i administered in a real-world setting exhibits a similar toxicity profile but higher incidence of treatment discontinuation compared to randomized trials. Efficacy of CDK4/6i among patients pretreated with multiple therapy lines is markedly reduced.